The effects of auditory stimulation on heart rate variability in healthy individuals with normal hearing and with hearing loss: a systematic review and meta-analysis - Silva, Bárbara Cristiane Sordi; Araújo, Eliene Silva; Valenti, Vitor Engrácia [UNESP]; Jacob, Lilian Cássia Bórnia; de Freitas Alvarenga, Katia (FapUNIFESP (SciELO), 2024)
Purpose: To analyze the effects of auditory stimulation on heart rate variability (HRV) indices in healthy individuals with normal hearing and with hearing loss, regardless of type and/or grade, by means of a systematic review. Research strategies: This is a systematic review with a meta-analysis that addresses the following question: in healthy individuals with normal hearing and/or with hearing loss, what are the effects of auditory stimulation on HRV indices in comparison to silence? We consulted the Cochrane Library, Embase, LILACS, PubMed, Web of Science, and Scopus databases and the gray literature (Google Scholar, OpenGrey, and ProQuest). Selection criteria: There were no restrictions as to period or language of publication. Data analysis: We identified 451 records, an additional 261 in the gray literature, and five studies in a search through the references, resulting in a total of 717 records, with 171 duplicate records. After screening the titles and abstracts of 546 studies, we excluded 490 and considered 56 studies in full to assess their eligibility. Results: Nine of these studies were included in the systematic review, eight of which were suitable for the meta-analysis. Conclusion: It is suggested that auditory stimulation may influence the RMSSD, pNN50, SDNN, RRTri and SD2 indices of HRV in healthy adults with normal hearing.
Keywords: Acoustic Stimulation; Autonomic; Hearing; Nervous System; Physiology; Systematic Review